Poisson measure as a spectral measure of a family of commuting selfadjoint operators, connected with some moment problem - Berezansky, Yu. M. (Methods of Functional Analysis and Topology, 2016)
It is proved that the Poisson measure is a spectral measure of some family of commuting selfadjoint operators acting on a space constructed from some generalization of the moment problem.